2021
DOI: 10.1039/d0fo02708a
|View full text |Cite
|
Sign up to set email alerts
|

In vitrogastrointestinal digestion and simulated colonic fermentation of pistachio nuts determine the bioaccessibility and biosynthesis of chronobiotics

Abstract: Chronodisruption leads to obesity and other metabolic disorders that food-derived chronobiotics such as phytomelatonin (PMT), phenolic compounds (PCs) and dietary fiber rich pistachios may help to alleviate. We evaluated the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…While there may be some discrepancy in melatonin in plant foods due to growing and harvesting conditions, there remains some debate about whether pistachios supply this amount of melatonin. Despite these inconsistencies, pistachios still feature prominently on the list of melatonin-containing foods and may have chronobiotic potential [ 234 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…While there may be some discrepancy in melatonin in plant foods due to growing and harvesting conditions, there remains some debate about whether pistachios supply this amount of melatonin. Despite these inconsistencies, pistachios still feature prominently on the list of melatonin-containing foods and may have chronobiotic potential [ 234 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…FAD produced the highest total SCFAs, followed by FAD‐E at 24 h incubation (110.6 and 106.3 mM/L, respectively). Since those values are similar to or even higher than those from common beans (Campos‐Vega et al., 2009), spent coffee grounds (light and dark roasted) (López‐Barrera et al., 2016), and pistachio nuts (Dufoo‐Hurtado et al., 2021), it is suggested that the insoluble fiber of FAD and FAD‐E CPH (their predominant dietary fiber component) is highly fermentable. Recently, processing has been suggested to boost insoluble dietary fiber fermentability.…”
Section: Resultsmentioning
confidence: 94%